(untitled) (International Journal of Engineering and Computer Science, 2014)
With an increase in the amount of volume of data in networks, the traditional storage architecture is greatly challenged. Today, SAN (storage area network) emerges as the main technology of network storage. The main inter networking technology of SAN is the fibre channel. But now with increasing demand for mirroring solutions for small & medium sized businesses, the high implementation costs, lack of trained staff and poor interoperability of fibre channel have proposed iSCSI to be a cost effective and viable alternative of fibre channel. Mirroring provides excellent solution for disaster-recovery, high data availability and business continuity. Synchronous mirroring or asynchronous mirroring enables customers to have an instantaneous recovery and eliminate loss of access to storage during disasters. But the cluster mirroring can transform your existing server storage into high availability storage system. The cluster mirroring tries to reduce the response-time and provide high availability storage. In this paper, we explore the details of iSCSI and attempt to evaluate the performance of iSCSI SAN and show that it can be performed satisfactorily and economically, without requiring the costlier fibre channel option